URBAN BIRD ECOLOGY: RELATIONSHIP OF THE PLANTS, WEATHER AND NOISE WITH THE BIRD BIODIVERSITY IN THE IQUITOS CITY, PERU - ANGULO PÉREZ, Natalia C. (2017)
Urban ecology provides guidelines for urban development policies, so that human societies live in healthier and more natural environments. Birds are good indicators of natural ecosystems, for this reason with the aim of determining the relationship of plants, climate and noise with the biodiversity of urban birds in the city of Iquitos (Peru), the method of counting by points was used in six of the main squares of the city. The sampling design in each square consisted of four observation points, and information was collected during three consecutive days, from 6:00 a.m. to 9:00 h and 16:00 to 18:00 h. The richness of birds was of 50 species, with greater abundance of Columba livia, Coragyps atratus and Tyrannus savana, and the plant richness was of 19 species, with dominance of Adonidia merrillii, Elaeis oleifera, Livistona chinensis and Ficus benjamina. The environmental temperature between the squares do not differ, but there was in the soil temperature, relative humidity and noise. There is a relationship between the abundance index of carnivorous birds and the richness of plant species in general, native plants and richness of trees species. The presence of plants, especially tall trees, would provide a greater supply of food, perching and nesting sites for carnivorous bird species. The greater the number of carnivorous species in an urban environment, the greater the advance towards a green city.